1990
DOI: 10.1172/jci114913
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological identification of alpha- and beta-intercalated cells and their distribution along the rabbit distal nephron segments.

Abstract: By cable analysis and intracellular microelectrode impalement in the in vitro perfused renal tubule, we identified a-and f,-intercalated (IC) cells along the rabbit distal nephron segments, including the connecting tubule (CNT), the cortical collecting duct (CCD), and the outer medullary collecting duct in the inner stripe (OMCDj)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
137
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(156 citation statements)
references
References 47 publications
18
137
1
Order By: Relevance
“…Our present approach is therefore noteworthy in that the stable puncture of the collecting duct cells of mammalian kidney can finally be accomplished. The value for Yb observed in the present study is as large as that reported by other investigators (Koeppen et al 1983; Schlatter and Schafer 1987; Sansom et al 1989;Muto et al 1990). We did not use differential phase contrast optics in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Our present approach is therefore noteworthy in that the stable puncture of the collecting duct cells of mammalian kidney can finally be accomplished. The value for Yb observed in the present study is as large as that reported by other investigators (Koeppen et al 1983; Schlatter and Schafer 1987; Sansom et al 1989;Muto et al 1990). We did not use differential phase contrast optics in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Because a moderate 01 -conductance exists in the basolateral membrane of the CNT cell (Yoshitomi et al 1988;Muto et al 1990), the observed hyperpolarization may reflect the reduction of intracellular Cl-concentration caused by inhibition of Clentry from the apical membrane of this type of cell. 5-8666 did not show any additive effect to TOM.…”
Section: Discussionmentioning
confidence: 99%
“…They include amiloride sensitive Na+ channel, Na+/H+ antiport, HC03-/C1-antiport and simple passive diffusion through paracellular pathway. Especially the HC03-/Cl-antiport which is mainly operated in the fl-IC cell may contribute to a large fraction of C1-flux in the CNT (Muto et al 1990). This is the reason why only small fraction of Cl-flux was inhibited by 5-8666 or TCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations